Stereoselective [4+2]‐Cycloaddition with Chiral Alkenylboranes. (11th May 2020) - Ni, Dongshun; Witherspoon, Brittany P.; Zhang, Hong; Zhou, Chen; Houk, K. N.; Brown, M. Kevin
Abstract: A method for the stereoselective [4+2]‐cycloaddition of alkenylboranes and dienes is presented. This transformation was accomplished through the introduction of a new strategy that involves the use of chiral N‐protonated alkenyl oxazaborolidines as dieneophiles. The reaction leads to the formation of products that can be readily derivatized to more complex structural motifs through stereospecific transformations of the C−B bond such as oxidation and homologation. Detailed computation evaluation of the reaction has uncovered a surprising role of the counterion on stereoselectivity. Abstract : Stereoselective [4+2]‐cycloaddition of alkenylboranes and dienes was accomplished through the introduction of chiral N‐protonated alkenyl oxazaborolidines as dieneophiles. The reaction gives products that can be readily derivatized to more complex structural motifs through stereospecific transformations of the C−B bond such as oxidation and homologation. DFT calculations uncovered a surprising effect of the counterion on stereoselectivity.